Comparison of Microphototrophic Communities Living in Different Soil Environments in the High Arctic - Pushkareva, Ekaterina; Wilmotte, Annick; Láska, Kamil; Elster, Josef (Frontiers in Ecology and Evolution, 2019)
The Arctic region undergoes rapid climate change resulting in soil warming with consequent changes in microbial community structure. Therefore, it is important to gain more knowledge on the pioneer photosynthetic microorganisms and their relations to environmental factors. Here we provide a description of the community composition of microbial phototrophs in three different types of soils in the High Arctic (Svalbard): vegetated soil at a raised marine terrace, biological soil crust (BSC) at high elevation, and poorly-developed BSC in a glacier foreland. The studied sites differed from each other in microclimatic conditions (soil temperature and soil water content), soil chemistry and altitude. Combining morphological (cell biovolume) and molecular methods (NGS amplicon sequencing of cyanobacterial 16S rRNA and eukaryotic 18S rRNA sequences of isolates), we studied the diversity and biovolume of cyanobacteria and eukaryotic microalgae. The results showed that cyanobacteria prevailed in the high altitude BSC as well as in pioneering BSC samples in glacier foreland though with lower biomass. More specifically, filamentous cyanobacteria, mainly Leptolyngbya spp., dominated the BSCs from these two localities. In contrast, coccoid microalgae (green and yellow-green algae) had higher biovolume in low altitude vegetated soils. Thus, the results of this study contribute to a better understanding of microphototrophic communities in different types of Arctic soil environments.